If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23.882 = -5.6 + -7.34x + -1.4 Reorder the terms: -23.882 = -5.6 + -1.4 + -7.34x Combine like terms: -5.6 + -1.4 = -7 -23.882 = -7 + -7.34x Solving -23.882 = -7 + -7.34x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7.34x' to each side of the equation. -23.882 + 7.34x = -7 + -7.34x + 7.34x Combine like terms: -7.34x + 7.34x = 0.00 -23.882 + 7.34x = -7 + 0.00 -23.882 + 7.34x = -7 Add '23.882' to each side of the equation. -23.882 + 23.882 + 7.34x = -7 + 23.882 Combine like terms: -23.882 + 23.882 = 0.000 0.000 + 7.34x = -7 + 23.882 7.34x = -7 + 23.882 Combine like terms: -7 + 23.882 = 16.882 7.34x = 16.882 Divide each side by '7.34'. x = 2.3 Simplifying x = 2.3
| 615=205t | | 2x+3y+5x+8y= | | 4+3(y-8)=y+3y | | -18+5x=17x | | 4x+24=4.6x | | 8(2t+1)-(t-9)=52-8t | | 8(x-1)=(3x+7) | | 6L+49=7 | | 15=2m+-9 | | X^9x+6=0 | | 2(v+5)=-3v+25 | | 5k+14=-36 | | 2b+-9=-3 | | 1=-8+3n | | 7x^2-22+3=0 | | 2a^2+11ab+15b^2= | | -4(x+5)=2(x+2) | | 9x-2=(x-5)(9x+4) | | 2+3x=-3+x | | 6x^4+7x^3-89x^2-112x+48=0 | | 4j+20=4 | | f(x)=x^2+7x+11 | | 5(2(4)-7)-3(3(4)-10)+4= | | 14+16=16+n | | 12(x+5)=13y+2 | | 4i+19=-13 | | tablefory=3x-2 | | 63=x+(x-7) | | 15.5+(3.5+10)=(15.5+n)+10 | | 6x-5y-30=0 | | 2y+-7=13 | | D=110-30 |